STUDY OF THE EFFECTIVENESS OF SORTING WASTE CONTAINERS IN BANDA ACEH CITY - Irda Yunita; Muhammad Nizar; Zaenal Abidin (Jurnal Inovasi Pendidikan dan Sains, 2022)
Community interest in the city of Banda Aceh is very low in disposing of waste according to the instructions for the 4 sorting and 2 sorting containers. This research was conducted to analyze the effectiveness and understanding of the community about sorting waste containers in the city of Banda Aceh. This research is a type of field research with mixed methods combining qualitative and quantitative research. The data taken is in the form of primary and secondary data. The sampling technique used in this study was simple random. Based on the results obtained by researchers, the average effectiveness of 4 sorting containers is 22% divided into 6 locations including location I which is 27%, location II 23%, location III 17%, location IV, 21%, location V 19%, and location VI 25% and the percentage of conformity of the marks on the 4 sorting containers, namely 33% organic waste, 25% recyclable waste, 5% reuse waste and 18% other waste. The average effectiveness of 2 sorting containers is 35%, divided into 3 locations namely location I which is 37%, location II 38, location III 31% and the percentage of suitability of markings namely wet waste 48% and dry waste 21%. The community's understanding is still low regarding the instructions on the 4 sorting container (reuse) while the community's understanding regarding the 2 sorting container is quite good. Keywords : Effectiveness, Sorting Container, Waste Composition, Public Understanding